Voto ideológico, ¿por qué los latinoamericanos votan por la izquierda o la derecha? - Torrico Terán, Mario Alejandro; Solís Delgadillo, Diego (El Colegio de México A.C., 2019)
The discussion of the causes of the turns to the left or the right in Latin America is an extensive one, and comparative electoral studies in the region have multiplied. However, due to the fact that they are analyzed in isolation, their contribution to understanding why people vote for the alternatives at one end of the ideological spectrum or the other is limited. This paper examines the ideological voting behavior of Latin Americans between 1996 and 2016, and we find that positions for or against the United States and the ideology of voters are the principal factors to explain this, together with social class, trust in political institutions, the ideology of the current government and the gender of the voter. Belonging to an indigenous group tends to favor a vote for left-wing alternatives when this division has previously been politicized. However, there are very large national variations compared to the regional trends, indicating that it is a very heterogeneous region.